The Utilization of Digital Technology in Transforming Banking Institutional Services (Case Study: Blu by Bca Digital) - Fauziah, Khayrunisa; Zahrani, Sabrina Alifia; Kinanthi, Sabina Titis; Nabila, Zahra Arij; Aisyah, Nabila Nuur (UMSU, 2025)
The development of digital technology is now occurring across various fields, including banking services. Changes in consumer behavior that increasingly desire fast, efficient, and technology-based services become both a challenge and an opportunity for the banking industry to innovate. The main problem raised in this research is how digital technology affects the transformation of banking services and forms new patterns of social interaction between banks and customers, especially among the younger generation. This study aims to examine the utilization of digital technology in banking services through a case study of Blu by BCA Digital, a digital bank that operates fully online without physical branch offices. The method used is a descriptive case study with a qualitative approach referring to Andreas Hepp’s theory of mediatization. Data were collected through secondary sources such as journal articles, official pages, Blu’s social media posts, and observations of Blu’s application features and interface. The results indicate that Blu by BCA Digital not only facilitates financial activities but also mediates social practices, shapes new habits in financial management, and creates a digitally based social structure. The mediatization process is visible from two aspects: materialization through the use of technology and digital infrastructure, and institutionalization through the emergence of new norms and expectations in financial services. In conclusion, Blu is not merely a financial aid tool but also an agent of change that reflects a paradigm shift in social interactions around banking, also supported by adaptive public regulations and policies responsive to the developments of the digital era.